Das Ende des repräsentativen Staates? Demokratie am Scheideweg - The End of the Representative State? Democracy at the Crossroads Eine Deutsch-Südafrikanische Perspektive - A German-South African Perspective - Schaks, Nils (Nomos Verlagsgesellschaft mbH & Co. KG, 2016)
The legitimacy of the state's authority is in crisis, as one is informed from all quarters. The future of representative democracy is in danger, and the era of post-democracy has been proclaimed. One of the most pressing constitutional and policy discussions in recent years has accordingly been whether, and to what extent, the representative system has reached its limits and how democracy can be revitalised. The debate has been ignited at the parliamentary as well as at the administrative level. This phenomenon can be observed in Germany and South Africa alike. Despite the differences between South Africa and Germany, both States' constitutions provide for a federal parliamentary system and a powerful constitutional court. The conference proceedings develop possible solutions for solving the challenges to the principle of democracy. After the initial diagnosis of the loss of the legitimation of the representative state, possible cures inherent in the representative system itself are explored. In a further step, it is asked to what extent more participation on the legislative as well as the executive level can help to strengthen the legitimation of the state.